Kendali Pid Dan Logika Fuzzy Untuk Optimalisasi Pergerakan Mobile Robot - Ibnu Mas’ud2, M.Fahmi; Hafidz, M. Nasrul; Harianto, Harianto; Cristian W., Madha (Journal JCONES, 2012)
KRI (Indonesian Robot Contest) is one of the race-level colleges both private and state in Indonesia. Most robots are contest  is the type of mobile robot. Obstacles often encountered in the race KRI is the intensity of light that enters the sensor photodioda causing impaired. To overcome this optocoupler can be used with this sensor the robot can walk with relying on the motor right and left motor. Optocoupler is issuing digital voltage sensor by exploiting holes contained disc motor. Distance and time the robot is used to analyze how much the speed of the robot by using fuzzy methods, while the method of PID is used to control the motor rotation right and left in order to go hand in hand and the same. Programming is used to enter the program to a minimum system  is to use a software system codevision Avr.   Keywords : Photodiode, microcontroller, Optocoupler, Fuzzy method, PID method, Codevision Avr.